2011
DOI: 10.1016/j.rbmo.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Condoms, HIV and the Roman Catholic Church

Abstract: For decades, the Roman Catholic Church opposed use of condoms to prevent spread of sexually transmitted infections (STI) because of their contraceptive effect. In 2009, Pope Benedict XVI said that widespread use of condoms could worsen the situation, a position rejected as 'unscientific'. Recently, however the Pontiff stated that because the Church considers acts of prostitution and homosexuality to be gravely immoral and disordered, in such specific cases use of a condom might become an initial step in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…However, it is possible that people may believe that their destinies are decided by God and therefore take fewer precautions. It has been shown that personal sexual behaviors and cultures are sometimes related to religion [1921]. Hence, education about HIV transmission and prevention should be discussed with religious leaders so they can deliver appropriate messages to MSM and their partners or families.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that people may believe that their destinies are decided by God and therefore take fewer precautions. It has been shown that personal sexual behaviors and cultures are sometimes related to religion [1921]. Hence, education about HIV transmission and prevention should be discussed with religious leaders so they can deliver appropriate messages to MSM and their partners or families.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the theme of effectiveness occurred primarily in connection with control strategies for sexually transmittable epidemics. For instance, there is a risk that a control strategy based on contraceptives may be ineffective when no adequate support, counseling, or guidance is provided [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observations outlined above, it appears reasonable to speculate that the JZ is exquisitely sensitive to pregnancy‐associated hormonal and embryonic signals. If so, failure of the JZ to remodel in early pregnancy may be predictive of subsequent failure or even obstetrical complications such as preterm labor11.…”
Section: Ultrasound Assessment Of Peri‐implantation Eventsmentioning
confidence: 99%
“…Human placenta formation, however, involves not only trophoblast invasion of the maternal decidua but also of the inner layer of the myometrium, a highly specialized uterine structure known as the junctional zone (JZ). Importantly, trophoblast invasion of the decidua and JZ, which forms the placental bed, is not only interstitial but also intravascular9–11. In fact, this process of intravascular trophoblast invasion critically controls the transformation of high‐resistance, low‐capacity spiral arteries into low‐resistance, high‐capacity vessels of pregnancy9, 12.…”
Section: Introductionmentioning
confidence: 99%